Peran Guru Dalam Peningkatan Kualitas Belajar Peserta Didik Pada Pembelajaran Daring Di Madrasah Ibtidaiyah - Wulandani, Tri Budi; Humaidi, Rif’an (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2021)
In the teaching and learning process, teachers are required to be able to carry out their role to the fullest as a motivator and initiator in an effort to maintain and at the same time increase the enthusiasm of students to learn. Especially in the Covid-19 pandemic situation which requires educational institutions to carry out online learning. This study aims to discuss the teacher's role as a motivator and the teacher's role as an initiator in improving the quality of student learning in online learning at Madrasah Ibtidaiyah Ma'arif Condro Jember. This research uses qualitative research methods and the type of research is a case study. Data collection techniques using observation, interviews and documentation. The validity of the data using source triangulation and technical triangulation. Meanwhile, data analysis uses data condensation, data presentation and verification/conclusion. The results of this study indicate: 1) The teacher's role as a motivator in improving the quality of learning in online learning, namely: providing opportunities for students to play an active role in learning, providing reinforcement, praise or verbal appreciation, teachers listening to students' concerns and wishes to bond. good relationship between teachers and students. 2) The role of the teacher as an initiator in improving the quality of learning in online learning, namely: utilizing information and communication technology such as Whatsapp, Facebook, Google Meet and Google Form. Keywords: Teacher Role; Quality of Learning; Online Learning Dalam proses belajar mengajar, guru dituntut untuk mampu melaksanakan perannya secara maksimal menjadi motivator dan inisiator dalam upaya menjaga dan sekaligus meningkatkan semangat belajar peserta didik. Terlebih dalam situasi pandemi Covid-19 yang menuntut lembaga pendidikan untuk melaksanakan pembelajaran secara Daring. Penelitian ini bertujuan untuk membahas tentang peran guru sebagai motivator dan peran guru sebagai inisiator dalam meningkatan kualitas belajar peserta didik pada pembelajaran daring di Madrasah Ibtidaiyah Ma’arif Condro Jember. Penelitian ini menggunakan metode penelitian kualitatif dan jenis penelitiannya adalah studi kasus. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Keabsahan data menggunakan triangulasi sumber dan triangulasi teknik. Sedangkan analisis data menggunakan kondensasi data, penyajian data dan verifikasi/kesimpulan. Hasil penelitian ini menunjukkan: 1) Peran guru sebagai motivator dalam meningkatkan kualitas belajar pada pembelajaran daring yaitu: memberikan kesempatan kepada peserta didik untuk berperan aktif dalam pembelajaran, memberikan penguatan, pujian atau apresiasi secara verbal, guru mendengarkan keresahan dan keinginan peserta didik agar terjalin ikatan yang baik antara guru dan peserta didik. 2) Peran guru sebagai inisiator dalam meningkatkan kualitas belajar pada pembelajaran daring yaitu: memanfaatkan teknologi informasi dan komunikasi seperti Whatsapp, Facebook, Google Meet dan Google Form. Kata Kunci: Peran Guru; Kualitas Belajar; Pembelajaran Daring